Analysis of lncRNA-Mediated ceRNA Crosstalk and Identification of Prognostic Signature in Head and Neck Squamous Cell Carcinoma - Pan, Yunbao; Liu, Guohong; Wang, Dujuan; Li, Yirong (Frontiers in Pharmacology, 2019)
Long non-coding RNA (lncRNA) can act as ceRNA to regulate the expression of target genes by sponging miRNAs, and therefore plays an essential role in tumor initiation and progression. However, functional roles and regulatory mechanisms of lncRNAs as ceRNAs in head and neck squamous cell carcinoma (HNSCC) remains to be determined. In the current study, we explored a genome-wide analysis to confirm potential lncRNA-associated ceRNA network. The mRNAs, lncRNAs and miRNAs sequence profiles were downloaded from availably accessed The Cancer Genome Atlas (TCGA) database. Differential expressed (DE) RNAs was analyzed using the ‘edgeR’ package in R. Kaplan-Meier curve analysis was used to confirm the survival based on ‘survival’ package in R. Gene Ontology (GO) enrichment and KEGG pathway of targeted genes were analysed through DAVID and KOBAS software, respectively. A total number of 1081 DElncRNAs, 1889 DEmRNAs and 196 DEmiRNAs were identified. The analysis of the ceRNA network identified 61 DElncRNAs as functional ceRNAs whose dysregulated expression will lead to variation in tumorigenic or tumor-suppressive gene expression at the post-transcriptional level contributing to HNSCC. Furthermore, univariate and multivariate Cox regression analysis revealed that 10 DElncRNAs, 5 EDmiRNAs and 9 DEmRNAs can predict survival with high accuracy. In conclusion, through constructing the ceRNA network in HNSCC patients, we shall further improve the understanding of ceRNA network regulatory mechanisms and identify several new lncRNAs and miRNAs for acting as candidate prognostic biomarkers and potential therapeutic targets.